The Use of Eptifibatide Alone or in Combination With Heparin or Argatroban for Suspected Thrombosis in Patients With Left Ventricular Assist Devices. Issue 12 (16th June 2017) - Bitar, Abbas; Vijayakrishnan, Rajakrishnan; Lenneman, Andrew; Birks, Emma; Massey, Todd; Slaughter, Mark; Abramov, Dmitry
Abstract: Pump thrombosis and hemolysis in patients with left ventricular assist devices (LVADs) are associated with significant morbidity and mortality. Intensification of anticoagulation has been suggested as potential therapy, with mixed results. The aim of this study is to assess the safety and efficacy of adding eptifibatide with or without an anticoagulation agent in managing patients with LVAD presenting with hemolysis and suspected pump thrombosis. This retrospective single center study included all patients who presented with their first episode of suspected pump thrombosis and were treated with eptifibatide with or without an anticoagulant between March 1, 2011 and July 30, 2015. A total of 27 patients (23 HeartMate II, 4 HeartWare) were identified. The average age was 55 years (range 19–75) and time from implant to event averaged 513 days (range 35–1760). The average lactate dehydrogenase on presentation was 1111 and 63% of patients had power elevations. The average international normalized ratio (INR) on admission was 2.4, with INR of ≥2 in 21/27 patients. All patients received eptifibatide: 10 received eptifibatide only, 9 received eptifibatide and argatroban, and 8 received eptifibatide and heparin. Warfarin was continued in 25/27 patients. Overall, 21 patients (77.8%) were successfully treated medically, 5 (18.5%) underwent pump exchange, and 1 (3.7%) died. There were no differences in outcomes or complications between the three treatment groups. Despite initial success, 12/21 patients developed repeat episodes of hemolysis at 1 year. The 1‐year survival in the patients treated medically was 90% and surgically was 60%. Our experience indicates that medical therapy for hemolysis and suspected LVAD thrombosis with warfarin and eptifibatide alone or in combination with argatroban or heparin appears safe and may be effective, although the episodes of recurrent hemolysis after medical management remain high.